Activation of Peroxisome Proliferator-Activated Receptor-Gamma by Glitazones Reduces the Expression and Release of Monocyte Chemoattractant Protein-1 in Human Mesothelial Cells - Matthias Sauter; Kathrin Kastenmüller; Franziska Belling; Markus Wörnle; Roland Ladurner; Thomas Mussack; Thomas Sitter (Mediators of Inflammation)
Human peritoneal mesothelial cells (MC) play an important role in inflammatory processes of the peritoneal cavity by producing various cytokines and chemokines, such as monocyte chemoattractant protein-1 (MCP-1). The present study was designed to assess the effect of the peroxisome proliferator-activated receptor-gamma- (PPARγ-) activator rosiglitazone on the mesothelial MCP-1 expression and release. Primary cultures of MC were obtained from omental tissue. MCP-1 antigen concentrations were measured in the cell supernatant by ELISA and MCP-1 mRNA levels by real-time polymerase chain reaction. The presence of PPARγ on MC was assayed in a Western Blot analysis. MC constitutively express PPARγ. Activation of this receptor via rosiglitazone (0,1–10 μmol/L) resulted in significantly reduced amounts of mesothelial MCP-1 release as well as MCP-1 mRNA. The use of the PPARγ inhibitor GW-9662 could completely prevent the rosiglitazone effects. Rosiglitazone was also effective in reducing TNFα-induced enhanced secretion of MCP-1. Our findings indicate that glitazones are effective in reducing constitutive and TNFα-stimulated mesothelial MCP-1 mRNA expression and release.